Repetitively rated plasma relativistic microwave oscillator with a controllable frequency in every pulse; Plasma Physics Reports; Vol. 34, № 10 - Bogdankevich I. L.; Grishin D. M.; Gunin A. V.; Ivanov I. E.; Korovin S. D.; Loza O. T.; Mesyats G. A. Gennady Andreyevich; Pavlov D. A.; Rostov V. V.; Strelkov P. S.; Ul'yanov D. K. (2008, 2008)
В фонде НТБ ТПУ отсутствует